The relationship between workload, autonomy and social support towards work engagement among support service division staff at KPJ Puteri Specialist Hospital / Muhamad Sharir Zafiq Shahizan - Shahizan, Muhamad Sharir Zafiq (Faculty of Business and Management, 2019)
Work engagement has been one of the most primary dependent variable that many researchers studied for a long decade. The research objective is to examine whether workload, autonomy and social support have a significant relationship with work engagement. The Job Demand-Resource Model (JD-R) has been applied in this study. The target respondent in this study are the Support Service Division Staffs at KPJ Puteri Specialist Hospital. There are 148 staffs from different departments have been selected as a respondent for this research study. The collected data will be analyzed using Statistically Package for Social Science (SPSS) software which include the Descriptive analysis, Reliability analysis, Correlation analysis and Multiple Regression analysis. The result of this study revealed that only autonomy and social support have positive significant relationship toward the work engagement. Hence, this study will be useful to manager and leader of organization to have deeper understanding and broad knowledge of the importance of having engaged workers that leads to promote the good motivation and productivity, increase the profitability and improve the efficiency of organization.